SPECIFIC FEATURES AND SOLUTIONS OF SOCIAL REFORMS IN NEW UZBEKISTAN (Academicia Globe: Inderscience Research, 2024)
This article describes the specific features and solutions of social reforms in New Uzbekistan, the acceleration of reforms in our country, and the large-scale work being done to create New Uzbekistan.